Embolization of the uterine arteries in treatment of uterine myoma: the actual approach in current realities - Grishin I.I; Roshchina V.A; O.I. Kauseva; Yu.E. Dobrokhotova (LCC «Medicine-Inform», 2018)
Embolization of the uterine arteries in treatment of uterine myoma: the actual approach in current realities I.I. Grishin1, V.A. Roshchina1, O.I. Kauseva2, Yu.E. Dobrokhotova1 1 Pirogov Russian National Research Medical University, Moscow, Russian Federation 2 City Clinical Hospital No.1 named after N. I. Pirogov, Moscow, Russian Federation Myoma of the uterus is detected in up to 50% of women aged over 35 years. Uterine artery embolization is an actual, highly effective, minimally invasive, organ-preserving method of treatment of uterine myomas. The article describes the effects of UAE on clinical manifestations of uterine myomas and current treatment strategies. Attention is paid to the relativity and expediency, advantages of using UAE in treatment of uterine myomas. The need for an individual approach to the treatment of uterine myomas by UAE is highlighted. The efficacy of UAE in the treatment of combined pathology of uterine myomas is discussed. The effect of UAE on the quality of life of patients with uterine myoma is assessed. The review presents the results of studies carried out by various authors, the short-term and long-term outcomes. In some cases, the uterine artery embolization may be recommended as an alternative to surgery, and in the complex treatment of uterine myomas. Key words: myoma of uterus, embolization of uterine arteries, UAE, hysterectomy, endovascular surgery. For citation: Grishin I.I., Roshchina V.A., Kauseva O.I., Dobrokhotova Yu.E. Embolization of the uterine arteries in treatment of uterine myoma: the actual approach in current realities. Russian Journal of Woman and Child Health. 2018;1(00):169-172.